William F. Elliott, Elliott's Supplement to the Indiana Revised Statutes of 1881, at 89 (1889) - (:unkn) unknown (My University, 1885)
§ 338: Prohibited the manufacture sale, exposure for sale, giving away as a prize or reward, any toy pistol or device that uses exploding caps, wafers, or other explosive compounds. Violators guilty of a misdemeanor, fined not less than ten nor more than fifty dollars, or imprisoned in county jail not less than ten nor moe than twenty days.
Keywords: TRANSFER, MANUFACTURE & POSSESSION - TOYS AND EXPLOSIVES